Improving 2D resolution in geosynchronous SAR via spatial spectrum synthesis: method and verification - Chen, Xinyan; Chen, Zhiyang; Li, Yuanhao; Hu, Cheng; Dong, Xichao; Hobbs, Stephen (Institute of Electrical and Electronics Engineers (IEEE), 2024)
Geosynchronous synthetic aperture radar (GEO SAR) has the advantages of a short revisit time and a large beam footprint. Enhancing spatial resolution has become a hotspot in spaceborne SAR research areas. The existing designs of GEO SAR suffer from the problem of poor resolution (greater than 10 m) and cause low-precision observation in urban areas. First time, this article points out that GEO SAR has the ability to improve the two-dimensional (2-D) resolution of SAR images by spatial spectrum synthesis based on 2-D baselines, and proposes models and a signal processing method involved in GEO SAR spectrum synthesis. The 2-D spatial baselines of GEO SAR are analyzed and evaluated first based on satellite software and real ephemeris from Beidou Inclined Geosynchronous Orbit (IGSO) navigation satellites to demonstrate the potential of 2-D resolution improvement. Then the analytical models of the spectral shape and relative spectral shift between GEO SAR images are derived. Furthermore, a 2-D spectrum synthesis algorithm suitable for GEO SAR is also proposed, where we use deramping operation instead of the traditional spectrum shifting process. Nonideal factors are considered in the processing of synthesized. In addition, performances of the proposed algorithm, including the resolution improvement factor, the amplitude fluctuation, and the critical baseline, are constructed. Finally, computer simulations and equivalent experiments based on Beidou IGSO navigation satellites verify the proposed algorithm.
Keywords: Geosynchronous synthetic aperture radar (GEO SAR); resolution improvement; spatial spectrum synthesis; two-dimensional (2-D) spatial baseline